Legal Power and Legal Competence Meaning, Normativity, Officials and Theories - Villa-Rosas, Gonzalo; Spaak, Torben (Cham : Springer International Publishing : Imprint: Springer, 2023)
This volume explores the concepts of legal power and legal competence in fourteen original, cutting-edge chapters by leading legal theorists. Legal power and legal competence are major topics in jurisprudence, as they concern a range of practices, common to all modern legal systems, that empower individuals to bring about changes in the respective system by changing their own legal position or the legal positions of others. This compilation covers five broad themes. The chapters in the first section address open questions on the meaning of legal power and legal competence, while those in the second tackle problems regarding their normativity. The third section is devoted to specifically exploring the relationship between legal power and constitutive norms. The fourth focuses on the analysis of legal officials and legal offices, while the fifth and final section assesses various theories of legal power and legal competence.
1. Introduction -- I. The Meaning of 'Legal Powerʼ and 'Legal Competence -- 2. Capabilities, Powers and Competences -- 3. Expanding Agency and Borders of Competence -- 4. Structures of Legal Competences -- II. The Normativity of Legal Power and Legal Competence -- 5. Testing the Utility of a Concept of Power-Conferring Norm: A Proposal -- 6. On the function of competence norms in a legal system -- III. Legal Power and Constitutive Rules -- 7. Recognition -- 8. Institutions and Constitutive Rules -- 9. -Constituting Power -- IV. Legal Officials and Legal Offices -- 10. Legal Offices and Legal Powers -- 11. A Hartian Account of Legal Officials -- 12. Authority and Reason in Issues of Legal Truth -- V. Theories of Legal Power and Legal Competence -- 13. An analysis of Jeremy Bentham's quasi-realistic model of legal competence -- 14. Merkl's Stufenbaulehre in the History of the Theory of Legal Power -- 15. Empowerment and the Act of Will in Hans Kelsen's General Theory of Norms.
Keywords: Law -- Philosophy; Law -- History; Theories of Law, Philosophy of Law, Legal History